Tunable loop filter in fractional-N frequency synthesizer for wireless applications - Kit G.L.; Hamid F.A.; Ahmed S.K. (2023)
A tunable loop filter in fractional-N frequency synthesizer is proposed and analyzed. The proposed concept allows designer to fine tune the loop bandwidth based on current injection into the loop filter. Fine tuning feature can be achieved with the utilization of a voltage-controlled transconductance component. The analysis and simulation results are presented for this technique. It shows that the frequency synthesizer employing the proposed tunable loop filter allows designer to have a fine control on the loop bandwidth and lock time of the system. 2012 IEEE.